2020
DOI: 10.3390/jcs4030121
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Facile Synthesis of Pt Nanoparticles Supported on Ketjen Black by Solution Plasma Sputtering as Bifunctional HER/ORR Catalysts

Abstract: Hydrogen evolution reaction (HER) and oxygen reduction reaction (ORR) are two core electrochemical processes involved in hydrogen fuel cell (HFC) technology. ORR is a cathodic reaction occurring in HFC, whereas HER can convert the H2O byproduct from HFCs into H2 gas via water splitting. Platinum (Pt)-based catalysts are the most effective catalysts for both reactions. In this work, we used a fast, facile, and chemical-free method, called solution plasma sputtering (SPS), to synthesize Pt nanoparticles supporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…This research laid the foundation for the production of platinum-based catalysts using plasma (Figure 2b-d). Mani-Late et al [30] doped Pt nanoparticles onto carbon black (KB) through solution plasma sputtering, obtaining Pt/KB materials. As the discharge time increased from 5 minutes to 20 minutes, the loading of Pt nanoparticles increased from 5.5 wt.% to 17.9 wt.%.…”
Section: Platinum-based Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…This research laid the foundation for the production of platinum-based catalysts using plasma (Figure 2b-d). Mani-Late et al [30] doped Pt nanoparticles onto carbon black (KB) through solution plasma sputtering, obtaining Pt/KB materials. As the discharge time increased from 5 minutes to 20 minutes, the loading of Pt nanoparticles increased from 5.5 wt.% to 17.9 wt.%.…”
Section: Platinum-based Catalystsmentioning
confidence: 99%
“…This research laid the foundation for the production of platinum‐based catalysts using plasma (Figure 2b–d). Mani‐Late et al [30] . doped Pt nanoparticles onto carbon black (KB) through solution plasma sputtering, obtaining Pt/KB materials.…”
Section: Application Of Plasma Techniques In Cathode Materialsmentioning
confidence: 99%
“…Besides, Chitlada et al obtained Pt NPs supported by Ketjen Black (KB) as the matrix through solution plasma sputtering (SPS) method, wherein the loading capacity of Pt NPs on KB could be easily controlled from 5.5% to 17.9 wt.% by adjusting the discharge time from 5 to 20 min. [33] This ingenious approach requires no chemical reducing agent so that the obtained NPs contain a clean surface without any organic layer hindering surficial active sites. The catalyst displayed an excellent ORR activity with an onset potential (E onset ) almost identical to the 20 wt.% Pt on Vulcan XC-72 (20% Pt/VC, 0.826 V), as well as more remarkable stability than 20 wt.% Pt/VC in 0.5 m H 2 SO 4 solution.…”
Section: Noble Metal Catalystsmentioning
confidence: 99%
“…Liu et al [46] have reported that the mass of Pt nanoparticles generated by erosion is mainly influenced by the diameter of the discharge electrodes and the discharge time, but no further details are given. Mani-Lata et al [47] observed an increase in the production of platinum nanoparticles with time in a solution containing Ketjen Black (KB) particles (30-50 nm in size), but the possible effect of the presence of KB was not described.…”
Section: Time Treatment Timementioning
confidence: 99%
“…Controlling size distributions is a key factor in the properties of materials made of nanoobjects. For instance, it is relatively simple to produce platinum nanoparticles with diameters around or even below 5 nm [46,47,59,122]. In contrast, manganese oxide nanoparticles are generally larger (between 20 and 100 nm typically) [9,60,91,94].…”
Section: Batteriesmentioning
confidence: 99%